2007
DOI: 10.1152/ajpregu.00725.2006
|View full text |Cite
|
Sign up to set email alerts
|

Placental insufficiency results in temporal alterations in the renin angiotensin system in male hypertensive growth restricted offspring

Abstract: Reduced uterine perfusion initiated in late gestation in the rat results in intrauterine growth restriction (IUGR) and development of hypertension by 4 wk of age. We hypothesize that the renin angiotensin system (RAS), a regulatory system important in the long-term control of blood pressure, may be programmed by placental insufficiency and may contribute to the etiology of IUGR hypertension. We previously reported that RAS blockade abolished hypertension in adult IUGR offspring; however, the mechanisms respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(137 citation statements)
references
References 60 publications
6
128
1
Order By: Relevance
“…There was a trend for increased total protein levels in sham rats treated with 5Ā mg/kg per day ELPā€VEGF, but it is possible that degradation products of the infused protein itself are being detected in this assay. It has been widely studied that the RUPP surgery induces fetal resorption and intrauterine growth restriction of the surviving pups 72, 73, 74, 75, 76. Fetal resorption and fetal growth restriction was observed in our study as well (TableĀ 1 and FigureĀ S3), validating the success of the RUPP procedure in our rats.…”
Section: Resultssupporting
confidence: 87%
“…There was a trend for increased total protein levels in sham rats treated with 5Ā mg/kg per day ELPā€VEGF, but it is possible that degradation products of the infused protein itself are being detected in this assay. It has been widely studied that the RUPP surgery induces fetal resorption and intrauterine growth restriction of the surviving pups 72, 73, 74, 75, 76. Fetal resorption and fetal growth restriction was observed in our study as well (TableĀ 1 and FigureĀ S3), validating the success of the RUPP procedure in our rats.…”
Section: Resultssupporting
confidence: 87%
“…123 In a larger study of 19-year-olds who were very preterm, stratified by weight for gestational age, birth weight correlated negatively with serum creatinine and albuminuria and positively with GFR. 124 These results are consistent with those of others, but as has been shown in animal studies, pro- Renal dysfunction Increased renal vascular reactivity 1renal artery response to ā¤-adrenergic stimuli and sensitivity to adenylyl cyclase in growth-restricted rats 184,186,187 Altered vascular reactivity 2flow-mediated dilation in LBW children 107,[188][189][190] 1uric acid Endothelial dysfunction Impaired vascular structure and capillary density Altered RAS Administration of inhibitors of RAS abrogates later hypertension 4,30,111,177,191 Administration of angiotensin II causes increased hypertensive response Evidence of expression of AT1R and AT2R and ACE activity are divergent at different stages and in different models of programming Overall, programmed suppression of intrarenal RAS during nephrogenesis and postnatal upregulation of AT1R are most consistent Altered sodium handling 2fractional excretion of sodium 22,109,110,174,192 1expression of BSC1 and TSC 1expression of glucocorticoid receptor 1expression of glucocorticoid responsive ā£1 and ā¤1 subunits of Na/K-ATPase 1expression of NHE3 1expression of ā¤ and ā„ ENaC Increased sympathetic nervous system activity Renal denervation reduced systolic BP and sodium transporter expression 193 Catch-up growth/obesity Higher BP in children who catch up fastest 98,154 Reduced flow-mediated dilation with higher rate of weight gain AT1R, angiotensin subtype 1 receptor; AT2R, angiotensin subtype 2 receptor; BSC1, bumetanide-sensitive co-transporter; ENaC, epithelial sodium channel; NHE3, sodium hydrogen exchanger; RAS, renin-angiotensin system; TSC, thiazide-sensitive co-transporter.…”
Section: Measures Of Renal Functionsupporting
confidence: 84%
“…Experimental studies showed alterations in the renin angiotensin system in experimentally induced intrauterine growth-restricted individuals at adult age, and these differences were not present at younger age. 32 Several markers of the renin angiotensin system were increased in intrauterine growth-restricted subjects with hypertension. 32 Future studies are needed to identify possible Figure 2.…”
Section: Fetal and Early Childhood Growth And Childhood Kidneymentioning
confidence: 99%
“…32 Several markers of the renin angiotensin system were increased in intrauterine growth-restricted subjects with hypertension. 32 Future studies are needed to identify possible Figure 2. Associations of birth outcomes with kidney outcomes (n=6482).…”
Section: Fetal and Early Childhood Growth And Childhood Kidneymentioning
confidence: 99%